Dapsone induced exfoliative dermatitis: A case report - Roy, Rajat; Bhattarai, Anil; Shrestha, Prativa; Paudel, Upama; Parajuli, Sudip (Journal of College of Medical Sciences-Nepal, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> One 11 year old female attended dermatology OPD of College of Medical Sciences, Bharatpur. She was undergoing treatment with Dapsone for one month for Borderline lepromatous leprosy. There was history of dry scales for 3 weeks over trunk, buttock, face, back and lower extremities suggestive of Exfoliative Dermatitis. The patient was treated with Prednisolone with supportive therapy for one month. Recovery is good. Key words: Dermatology; lepromatous leprosy; exfoliative dermatitis. DOI: 10.3126/jcmsn.v6i2.3621 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 64-66